Immunogenicity, safety, and reactogenicity of combined reduced-antigen-content diphtheria-tetanus-acellular pertussis vaccine administered as a booster vaccine dose in healthy Russian participants: a phase III, open-label study. Issue 3 (4th March 2021) - Asatryan, Asmik; Meyer, Nadia; Scherbakov, Michael; Romanenko, Victor; Osipova, Irina; Galustyan, Anna; Shamsheva, Olga; Latysheva, Tatiana; Myasnikova, Tatyana; Baudson, Nathalie; Dodet, Monique; Xavier, Stebin; et al.
ABSTRACT: As vaccine-induced immunity and protection following natural pertussis infection wane over time, adults and adolescents may develop pertussis and become transmitters to unprotected infants. In Russia, diphtheria and tetanus but not pertussis-containing vaccines are registered for older children, adolescents, or adults. The reduced-antigen-content diphtheria toxoid, tetanus toxoid, and acellular pertussis (dTpa) vaccine ( Boostrix, GSK) was developed for booster vaccination of children ≥4 years of age, adolescents, and adults. A phase III, open-label, non-randomized study was performed in eight centers in Russia between January and July 2018. The objective of this study was to assess immunogenicity, reactogenicity and safety of a single dose of dTpa vaccine in healthy Russian participants ≥4 years of age (age categories 4–9 years, 10–17 years, 18–64 years, and ≥65 years). At 1 month post-booster vaccination, across all age groups, >99.0% of participants were seroprotected against diphtheria and tetanus and >96.0% of participants were seropositive for anti-pertussis antibodies. For all antibodies across all age groups, antibody GMCs increased from pre- to 1 month post-booster vaccination and booster responses to diphtheria (in 71.5% of participants), tetanus (85.3%), and pertussis antigens (≥85.6%) were observed. One serious adverse event that was not causally related to the study vaccine was reported. No fatal cases were reported throughout the study period. In conclusion, administration of the dTpa vaccine as a booster dose in healthy Russian participants induced a robust immune response to all vaccine antigens and was generally well tolerated across all age groups.